A study on the intervention of positive discipline on parenting self-efficacy and subjective well-being among Chinese parents - Wu, Maoqin; Mariamdaran, Saralah Devi A/P (Ricerche di Psicologia - Open Access, 2026)
Background: In contemporary China, parenting is characterized by high stress and authoritarian practices, leading to negative impacts on self-efficacy and well-being. Positive Discipline provides an alternative to improve family dynamics that is more in harmony with Chinese culture. The positive discipline method is appropriate for the Chinese culture owing to its focus on self-discipline and high academic achievement. The idea of positive discipline in recent years has emerged as a new effective positive parenting approach supporting both kind and firm parenting styles, contributing positively to child development. Aim: This study examines the impact of Positive Discipline on self-efficacy and subjective wellness of Chinese parents, focusing on culturally responsive psychological interventions. Methodology: A six-week quasi-experimental intervention with 62 parents from Fujian Province, China, utilised the validated Subjective Well-being Scale and the brief-parental-self-efficacy-scale-interactive. Data was analysed quantitatively through SPSS pre- and post-intervention by analysing the two variables self-efficacy and well-being. Results: Parents reported improved parenting self-efficacy, increased subjective well-being, therefore, a reduced stress post-intervention. There was a strong correlation showing the efficacy of the intervention in ensuring parental well-being in promoting a sense of parenting efficacy and subjective well-being. Conclusion: Positive Discipline nurtures self-efficacy in parenting and psychological well-being among Chinese parents. This would empower the parents to adopt a modern parenting style in Chinese society and adapt to the current parenting pressure. Incorporating PD into family support services might reduce parenting stress and improve emotional health.